Implementing Single-Item Screening for Drug Use in A Veterans Health Administration Outpatient Setting. Issue 4 (October 2018) - Hodgkin, Dominic; Gao, Wenwu; Merrick, Elizabeth L.; Drebing, Charles E.; Larson, Mary Jo; Horgan, Constance M.; Sharma, Monica; Petry, Nancy M.; Saitz, Richard
Background : Unhealthy drug use is a concern in many settings, including military and veteran populations. In 2013, the Veterans Health Administration (VHA) medical center in Bedford, Massachusetts, started requiring routine screening for unhealthy drug use in outpatient primary care and mental health settings, using a validated single question. Methods : This study used descriptive and multivariable analyses of VHA electronic records for patients eligible for the screening program ( N = 16, 118). The study assessed first-year rates and predictors of screening and of positive screens, both for drug use and for unhealthy alcohol use, for which screening was already required. Results : During the first year, 70% of patients were screened for unhealthy drug use and 84% were screened for unhealthy alcohol use. In multivariable analyses, screening for drug use was more likely for patients who had 8 or more days with VHA visits or were aged 40 or over. Patients with a prior drug use disorder diagnosis were much less likely to be screened. Three percent of patients screened for unhealthy drug use had a positive screen, and 14% of those screened for unhealthy alcohol use had a positive screen. Strong predictors of a positive drug use screen included a prior-year diagnosis of drug use disorder, any mental health clinic visits, younger age, or being unmarried. Conclusions : The drug screening initiative was relatively successful in its first-year implementation, having screened 70% of eligible subjects. However, it failed to screen many of those most likely to screen positive, thereby missing many opportunities to address unhealthy drug use. Future refinements should include better training clinicians in how to ask sensitive questions and how to address positive screens.